A novel model for predicting tight sandstone reservoir permeability. (11th November 2021) - Sun, Lili; Hao, Xining; Dou, Hongen; Adenutsi, Caspar Daniel; Liu, Wenli
In order to solve the problem of low accuracy of permeability prediction in tight sandstone reservoirs, two new parameters namely effective movable fluid saturation and capillary-bound fluid saturation were proposed, to quantitatively evaluate the flow capacity of reservoir fluids based on the analysis of the state of fluid occurrence in pore space. Nuclear magnetic resonance (NMR) and high-pressure mercury injection experiments were used to establish the relationships between permeability and the new parameters and a new permeability prediction model was proposed in tight sandstone reservoirs. The method was verified by comparing permeability computed using existing models and measured data from the field. The results showed that the proposed model in this paper gave R 2 and root mean square error values of 0.839 and 0.0428, respectively, which were better than that given by the SDR and the Coates models. Thus, the proposed model in this research significantly improved the accuracy of permeability prediction in tight sandstone reservoirs. This provides a new method for permeability prediction and field development in tight sandstone reservoirs. [Received: December 20, 2019; Accepted: December 16, 2020]